Rotational and blockage effects on a wind turbine model based on local blade forces. Issue 2 (1st May 2022) - Soto-Valle, R.; Gualtieri, M.; Bartholomay, S.; Manolesos, M.; Nayeri, C.N.; Bianchini, A.; Paschereit, C.O.
Abstract: This paper describes the results of an extended experimental campaign, reporting surface pressure measurement over one of the blades of the Berlin Research Turbine (BeRT), placed in a closed-loop wind tunnel facility. BeRT is a three-bladed horizontal axis wind turbine with a 3 m rotor diameter. The focus is, on the one side, on the three-dimensional effects experienced by the rotating blade, in comparison to 2D approaches by means of XFoil simulations and 2D blade section experiments. On the other side, the blockage effects are investigated between the wind turbine model, placed in the wind tunnel where a 40% blockage ratio is produced, and lifting line free vortex wake simulations, where wind tunnel walls are not considered. Additionally, CFD computations are added in the comparison, with simulations of the far-field and with the wind tunnel walls. The turbine model is studied at several operational conditions such as different blade pitch angles and turbine yaw misalignments. Results are presented in terms of local force components derived from the surface pressure measurements. It is shown that rotational augmentation is evident at the blade mid-span location despite the large blockage. Additionally, the blockage is noticed by means of an offset in both normal and tangential local forces conserving trends and features under axial inflow and yaw misalignments. It is found that the offset in forces can be counteracted by pitching the blades.